Facet-dependent catalytic activity of platinum nanocrystals for triiodide reduction in dye-sensitized solar cells - Zhang, B.; Wang, D.; Hou, Y.; Yang, S.; Yang, X.; Zhong, J.; Liu, Jian; Wang, H.; Hu, P.; Zhao, H.; Yang, H. (Nature Publishing Group, 2013)
Platinum (Pt) nanocrystals have demonstrated to be an effective catalyst in many heterogeneous catalytic processes. However, pioneer facets with highest activity have been reported differently for various reaction systems. Although Pt has been the most important counter electrode material for dye-sensitized solar cells (DSCs), suitable atomic arrangement on the exposed crystal facet of Pt for triiodide reduction is still inexplicable. Using density functional theory, we have investigated the catalytic reaction processes of triiodide reduction over {100}, {111} and {411} facets, indicating that the activity follows the order of Pt(111) > Pt(411) > Pt(100). Further, Pt nanocrystals mainly bounded by {100}, {111} and {411} facets were synthesized and used as counter electrode materials for DSCs. The highest photovoltaic conversion efficiency of Pt(111) in DSCs confirms the predictions of the theoretical study. These findings have deepened the understanding of the mechanism of triiodide reduction at Pt surfaces and further screened the best facet for DSCs successfully.